Tailoring H2O2 generation kinetics with magnesium alloys for efficient disinfection on titanium surface - Park, Jimin; Jang, Gun Hyuk; Jung, Yeon Wook; Seo, Hyunseon; Han, Hyung-Seop; Lee, Joonho; Seo, Youngmin; Jeon, Hojeong; Ok, Myoung-Ryul; Cha, Pil-Ryung; Seok, Hyun-Kwang; Lee, Kwan Hyi; et al. (Nature Publishing Group, 2020)
A new antibacterial strategy for Ti has been developed without the use of any external antibacterial agents and surface treatments. By combining Mg alloys with Ti, H2O2, which is an oxidizing agent that kills bacteria, was spontaneously generated near the surface of Ti. Importantly, the H2O2 formation kinetics can be precisely controlled by tailoring the degradation rates of Mg alloys connected to Ti. Through microstructural and electrochemical modification of Mg with alloying elements (Ca, Zn), the degradation rates of Mg alloys were controlled, and the H2O2 release kinetics was accelerated when the degradation rate of Mg alloys increased. With the introduction of an in vivo assessment platform comprised of Escherichia coli (E. coli) and transgenic zebrafish embryos, we are able to design optimized antibacterial systems (Ti-Mg and Ti-Mg-3wt% Zn) that can selectively eradicate E. coli while not harming the survival rate, development, and biological functions of zebrafish embryos. We envision that our antibacterial strategy based on utilization of sacrificial Mg alloys could broaden the current palette of antibacterial platforms for metals.